The analysis on how corporate image, service quality, customer satisfaction enhance customer loyalty towards Kopcel shoppe among members of KCB’s. Case study at Menara Celcom, Jalan Semarak, Kuala Lumpur / Nur Nazihah Raman - Raman, Nur Nazihah (2011)
The main objectives of this study were to identify attributes that influence Customer Loyalty and determine their relationships with Customer Loyalty. The variables includes in this research are Corporate Image, Service quality and Customer Satisfaction as independent variables and Customer Loyalty as the dependent variables. A survey questionaire which consisted of three parts to measure demographic profiles, three independent variables and one dependent variables was constructed based on items determined by past researcher. The questionnaire distributed by email. 408 respondents from member’s of KCB that working in Menara Celcom were selected as a sampling frame, only 192 of them respont the questionnaire given. All the findings in this research were analyzed by using SPSS 17.0. The result showed that all of the correlation between variables were significant and has positive relationship to each other. The highest correlation is customer satisfaction towards customer loyalty followed by corporate image towards customer loyalty . Since this research can be implemented to the new Kopcel Shoppe, so that the organization need to do something to upgrade the Corporate Image of new Kopcel Shoppe at Wisma Celcom